Gender Transformative Socio-Technical Innovation Bundles (GTSTIBs) scaling roadmap - Lutomia, Cosmas Kweyu; Nyamolo, Victor; Muriithi, Catherine; Ketema, Dessalegn; Nyaga, John Ndwiga; Njeru, Patrick Ndwiga; Nchanji, Eileen (2025)
This 48-month roadmap sets out how Embu County will scale gender-transformative socio-technical innovation bundles (GTSTIBs). It builds on 2022–2024 pilots, anchors delivery in CASSCOM, and integrates GTSTIBs into extension services and county budgets, with farmer co-creation throughout. The plan moves through four phases: laying foundations; expanding pilots and integrating services; countywide scale with stronger market links; and long-term sustainability. It details policy steps, monitoring and learning, and partnerships with private finance. Targeting will be inclusive of women, youth, and persons with disabilities. Clear adoption and impact targets will track empowerment, productivity, climate resilience, and nutrition as the program grows.